Coping Strategies in Swimming: The Role of Control in the Choice of Strategies - Hatzigeorgiades Αντώνης; Chroni Στυλιανή (Inquiries in Physical Education and Sport, 2003)
The purpose of the study was to explore coping strategies used by swimmers during competition and to examine whether control over the situation relates to the choice of coping strategies. Sixty six swimmers participated in the study. Participants were asked to indicate coping strategies they would use in two hypothetical situations, one relatively more controllable and one relatively less controllable. Four coping strategies were examined, two involving approach coping which were ‘active coping’ and ‘planning’, and two involving avoidance coping, which were ‘mental disengagement’ and ‘behavioral disengagement’. Results showed that swimmers use more approach and less avoidance coping during competition. However, it was also found that approach coping is used more in controllable situations in comparison to less controllable situations, whereas avoidance coping is used more in less controllable situations in comparison to controllable situations. The results of the study underline the importance of control in the selection of coping strategies, indicating that in order to avoid maladaptive consequences the continuous use of avoidance coping can cause, it is preferable not to expose swimmers in the pursuit of uncontrollable goals.